Sensitivity to Monoclonal Antibody 447–52D and an Open Env Trimer Conformation Correlate Poorly with Inhibition of HIV-1 Infectivity by SERINC5 - Angerstein, Aaron O. (Virology, 2020)
The host protein SERINC5 inhibits the infectivity of HIV-1 virions in an Env-dependent manner and is counteracted by Nef. The conformation of the Env trimer reportedly correlates with sensitivity to SERINC5. Here, we tested the hypothesis that the “open” conformation of the Env trimer revealed by sensitivity to the V3-loop specific antibody 447–52D directly correlates with sensitivity to SERINC5. Of five Envs tested, SF162 was the most sensitive to neutralization by 447–52D, but it was not the most sensitive to SERINC5; instead the Env of LAI was substantially more sensitive to SERINC5 than all the other Envs. Mutational opening of the trimer by substitution of two tyrosines that mediate interaction between the V2 and V3 loops sensitized the Envs of JRFL and LAI to 447–52D as previously reported, but only BaL was sensitized to SERINC5. These data suggest that trimer “openness” is not sufficient for sensitivity to SERINC5.